The Effect of Learning Interest on Student Learning Outcomes in Short Distance Running Class V at SD Negeri 112 Seluma - Novriansyah, Fahrison; Suwarni , Suwarni; Martiani, Martiani (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of interest in learning on student learning outcomes in class v short distance running at SD Negeri 112 Seluma. This research design uses a survey method with sampling techniques using total sampling with a sample size of 22 respondents, data analysis in this study using quantitative descriptive techniques with hypothesis testing using simple linear regression analysis. The variable value coefficient ???? of 0.841 states that every 1% increase in the value of learning interest will increase by 0.841. Based on the value of the correlation coefficient, the r value is 0.832, which means that variable X has a strong positive correlation with variable Y, the r square value is 69.3%. This means that interest in learning affects learning outcomes by 69.3% and 30.7% is influenced by other variables. Based on the value of ????ℎ???????????????????? greater than the value of ???????????????????????? = 2.07387 so that ????0 is rejected and Ha is accepted which means that there is an effect of learning interest on student learning outcomes in learning short distance running class V at SD Negeri 112 Seluma.